Microanatomical Nerve Architecture of 6 Mammalian Species: Is Trans-Species Translational Anatomic Extrapolation Valid?. Issue 5 (July 2018) - Server, Anna; Reina, Miguel A.; Boezaart, André P.; Prats-Galino, Alberto; Esteves Coelho, Marielle; Sala-Blanch, Xavier
Abstract : Background and Objectives: Various animal models have historically been used to study iatrogenic nerve injury during performance of conduction nerve blocks. Our aims were to compare the microstructures of nerves in commonly used species to those of humans and to explore the validity of the extrapolating these findings to humans. Methods: High-resolution, light-microscopic images were obtained from cross sections of sciatic nerves at their bifurcation from fresh rat, rabbit, pig, sheep, dog, and human cadavers. Various microanatomical characteristics were measured and compared between the species. P < 0.0033 indicated significant differences. Results: Forty-four samples were studied. There were some interspecies similarities, but the majority of the microanatomical measurements of all 5 species differed significantly from those of humans. Exceptions were rat fascicle cross-sectional area ( P = 0.367) and fascicle circumference ( P = 0.396); ratio of dog, pig, and sheep fascicle area to total nerve area (dog: P = 0.350; pig: P = 0.958; sheep: P = 0.052); and number of fascicles (pig: P = 0.454; sheep P = 0.077). Conclusions: Although some of the metrics could reasonably be expected to differ because of the size of the species—for example, nerve cross-sectional area—there was little microanatomical similarity between the sciatic nerves of humans and those of the nonprimate mammalian species studied. This may question the validity of some conclusions reached over the years by direct translation from these species to humans. Further studies on nerve function, intraneural injection, and microanatomy of nonhuman primate species are warranted.